FENOMENA BAHASA GAUL DALAM KACAMATA MORFOLOGIS, FONOLOGIS, DAN SINTAKSIS - Romadhianti, Rona (JURNAL PESONA, 2019)
The purpose of this research describe the slang among adolescents in Group-Whats up (WA), Instagram Status and Face book (FB) are examined based on the structure of morphological, phonological and syntactic. The theory of Sociolinguistics and Morfosintaksis used as a scalpel in the research. Sociolinguistic theory is used to analyze the factors that influence language and function usage whereas Morfosintaksis used to analyze the process of formation of the words in the